INTERNATIONAL LEGAL FRAMEWORK ON VIOLENCE AGAINST WOMEN : the need for reform. - McQuigg, Ronagh J. A. (ROUTLEDGE, 2026)
This book provides in-depth critical analysis of the international legal framework on violence against women and, crucially, the need for reform of this framework. Violence against women occurs in every state worldwide and constitutes one of the most prevalent human rights abuses at the global level. However, none of the UN treaties refer specifically to violence against women. The book argues that there is a pressing need for legally binding provisions to be adopted at the global level on this issue. Two forms which such provisions could take are considered. These are, firstly, an Optional Protocol to the UN Convention on the Elimination of All Forms of Discrimination Against Women; and secondly, a stand-alone UN treaty on violence against women. The book's intended audience includes academics and researchers from a wide variety of disciplines, such as human rights, international law, criminal law, criminology, social policy, gender studies and sociology; as well as practitioners and those in the voluntary sector who are working in the area of combating violence against women. The book could also be used beneficially on courses at both undergraduate and postgraduate levels which incorporate the topic of violence against women.
Keywords: United Nations. -- Committee on the Elimination of Discrimination Against Women.; Convention on the Elimination of All Forms of Discrimination against Women -- (1979 December 18); Convention on the Elimination of All Forms of Discrimination against Women -- (1979 December 18). -- Protocols, etc.; Gender-based violence.; Sex discrimination against women -- Law and legislation.; Women -- Violence against -- Law and legislation.; Women -- Crimes against -- Law and legislation.; Women (International law); Women's rights.; elektronické knihy; electronic books